Numerical modeling for effect on bund overtopping caused by a catastrophic failure of chemical storage tanks - Min, Dong Seok; Phark, Chuntak; Jung, Seungho (Korean Chemical Engineering Research, 2019)
− As the industry develops in Korea, the use of hazardous chemicals is increasing rapidly and chemical accidents are increasing accordingly. Most of the chemical accidents are caused by leaks of hazardous chemicals, but there are also accidents in which all the substances are released instantaneously due to sudden high temperature/pressure or defection of the storage tanks. This is called catastrophic failure and its frequency is very low, but consequence is very huge when it occurs. In Korea, there were 15 casualties including three deaths due to catastrophic rupture of water tank in 2013, and 64 instances of failures from 1919 to 2004 worldwide. In case of catastrophic failure, it would be able to overflow outside the bund that reduces the evaporation rate and following consequence. This incident is called overtopping. Overseas, some researchers have been studying the amount of external overflow depending on bund conditions in the event of such an accident. Based on the previous research, this study identified overtopping fraction by condition of bund in accordance with Korea Chemicals Controls Act Using CFD simulation. As a result, as the height increases and the distance to the facility decreases while meeting the minimum standard of the bund capacity, the overtopping effect has decreased. In addition, by identifying the effects of overtopping according to atmospheric conditions, types of materials and shapes of bunds, this study proposes the design of the bund considering the effect of overtopping caused by catastrophic failure with different bund conditions.
Keywords: Bund; Catastrophic Failure; CFD; Consequence Analysis; Overtopping; Simulation